Muslimah Label or Sharia-Compliant Brand? A Study on Kirei Salon and Spa Muslimah Bekasi Through The Lens of DSN-MUI Fatwa - Wibisono, Vina Fithriana; Arief, Suyoto; Rafifah, Fairuz Hasna (Universitas Muhammadiyah Surakarta, 2025)
The growing popularity of Muslimah-branded beauty services raises questions about the authenticity of their compliance with Sharia principles. This study aims to critically examine whether Kirei Salon and Spa Muslimah Bekasi, which adopts an Islamic branding strategy, operates in accordance with Fatwa DSN-MUI No.108/DSN-MUI/X/2016 on Guidelines for Organizing Tourism Based on Sharia Principles, particularly in the context of spa, sauna, and massage services. This research method employing a descriptive qualitative approach, data were collected through interviews with the salon owner, staff, and customers, as well as field observations and documentation analysis. The findings indicate that while Kirei Salon and Spa Muslimah effectively maintains female-only service and promotes modesty in branding, several operational practices do not fully align with the DSN-MUI fatwa. Notable discrepancies include the use of uncertified beauty products, the offering of certain non-compliant treatments (e.g., hair colouring, extensions), and the absence of properly segregated prayer facilities. These findings suggest that the Muslimah label functions more as a branding identity rather than reflecting full adherence to Sharia-compliant operational standards. This study contributes to the discourse on Islamic branding by highlighting the gap between religious label usage and actual Sharia compliance in the beauty service sector. It provides a critical lens for both business practitioners and regulators to reevaluate the standards and authenticity of Muslimah-oriented branding.